Sandifer syndrome misdiagnosed as refractory partial seizures in an adult. - Somjit S; Lee Y; Berkovic SF; Harvey AS (Epileptic disorders : international epilepsy journal with videotape, 2004)
We report a 27 year-old man with intellectual disability and no prior history of seizures who presented with episodes of abdominal pain, head/eye version and unresponsiveness that were misdiagnosed and treated as partial seizures. Associated vomiting and haematemesis led to the correct diagnosis and treatment of reflux oesophagitis. The episodes immediately resolved and a diagnosis of Sandifer syndrome was made. This is only the second report of Sandifer syndrome in adult, a movement disorder of unknown mechanism that occurs almost exclusively in young children, often misdiagnosed as epilepsy or episodic dystonia. (Published with videosequences).